2017
DOI: 10.1186/s13075-016-1212-x
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in gene expression and inflammatory proteins in systemic juvenile idiopathic arthritis patients on canakinumab therapy

Abstract: BackgroundCanakinumab is a human anti-interleukin-1β (IL-1β) monoclonal antibody neutralizing IL-1β-mediated pathways. We sought to characterize the molecular response to canakinumab and evaluate potential markers of response using samples from two pivotal trials in systemic juvenile idiopathic arthritis (SJIA).MethodsGene expression was measured in patients with febrile SJIA and in matched healthy controls by Affymetrix DNA microarrays. Transcriptional response was assessed by gene expression changes from bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
7
60
1
Order By: Relevance
“…These are conditions in which elevated IL-1 and IL-6 activity are considered to play a key role in disease pathogenesis, evidenced by clinical improvement following therapeutic antagonism of these cytokines (22)(23)(24)(25). The blood transcriptome of untreated JIA patients displayed elevated IL-1 and IL-6 bioactivity (fig 2A) (26), but this was not consistently evident in several RA blood transcriptome datasets (fig S1) (27)(28)(29).…”
Section: Il-1 and Il-6 Module Expression In Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…These are conditions in which elevated IL-1 and IL-6 activity are considered to play a key role in disease pathogenesis, evidenced by clinical improvement following therapeutic antagonism of these cytokines (22)(23)(24)(25). The blood transcriptome of untreated JIA patients displayed elevated IL-1 and IL-6 bioactivity (fig 2A) (26), but this was not consistently evident in several RA blood transcriptome datasets (fig S1) (27)(28)(29).…”
Section: Il-1 and Il-6 Module Expression In Chronic Inflammationmentioning
confidence: 99%
“…We used the elevated cytokine activity in the blood of JIA patients to test the hypothesis that therapeutic cytokine modulation would result in changes in cytokine bioactivity as determined by module expression. We made use of the blood transcriptome of JIA patients 3 days following administration of canakinumab, a human monoclonal antibody to IL-1β (26). Patients who had a therapeutic response to canakinumab showed elevated IL-1 module expression which reduced 3 days after canakinumab administration ( fig 3A).…”
Section: Il-1 and Il-6 Module Expression In Chronic Inflammationmentioning
confidence: 99%
“…JIA shows similarities to adult autoimmune diseases, and, indeed, genome-wide association studies identify a strong overlap in the common variants linked to autoimmune susceptibility and JIA susceptibility 1. JIA also has similarities to autoinflammatory diseases, such as genetic associations to innate inflammatory pathways2 and response to IL-1β blockade 3. The recent success in identifying monogenic causes of autoinflammatory diseases4 suggests that monogenic causes may also underlie a subset of patients with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) and monocytic cells from patients with active sJIA have been analyzed in gene expression studies and have been shown to have a variable RNA expression pattern in patients with sJIA compared to healthy controls, patients with other autoimmune diseases, and patients with other subtypes of JIA, with uneven results [ 4 , 5 ]. With the exception of a recent study looking at RNA expression in patient samples from two clinical trials of canakinumab, these studies have so far only used a cross-sectional approach, and patients with sJIA were not stratified according to their disease activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%